Unveiling AI Deployment and Social Support on Customer Value Co-Creation and Stickiness in Social Commerce: A PLS-SEM and NCA Approach - Catacutan, Zandro M.; Perlado, Christian Edwin M. (UI Scholars Hub, 2026)
Research Aims: This study examines AI deployment and social support in fostering customer value co-creation and customer stickiness towards S-commerce applications in online shopping. Design/Methodology/Approach: This study employed a cross-sectional survey design, incorporating purposive and snowball sampling, and a sample size of 625 participants. PLS-SEM and NCA were utilised to test the hypotheses of this study. Research Findings: The study results showed that AI deployment and social support were significant determinants and essential factors in facilitating customer value co-creation for S-commerce. However, it is not a prerequisite for maintaining customer stickiness in S-commerce. Customer value co-creation was found to have positive direct and mediating effects on customer stickiness, and to exhibit dynamic interrelationships with factors relevant to S-commerce applications in online shopping. Theoretical Contribution/Originality: This study comprehensively combined insights from customer-dominant logic theory, social support theory, AI-enabled VCC theory, and the SOR framework to identify the key determinants of customer value co-creation and customer stickiness towards social commerce applications in the Philippine online shopping context. Managerial Implication in the South East Asian Context: The study highlights how platform can enhance S‑commerce by integrating AI-driven features, social support mechanisms, and personalised assistance tools to improve navigation, engagement, and the overall customer experience, thereby fostering customer value co-creation and stickiness in S-commerce. Research Limitation & Implications: The study limited to its local setting which affect broader generalizability. The cross-sectional assessments mainly concentrated on customer value co-creation and stickiness in S-commerce including Facebook, Instagram, and TikTok. Future research may include cross-country comparisons, expanded analyses of AI-related outcomes, and multi-group analyses by customer segments.